Description of two new species and a new population of Mesobiotus cf. coronatus from Cotacachi-Cayapas National Park, Ecuador - Anastasiia Polishchuk; Pushpalata Kayastha; Dominika Młodzianowska; Martyna Michalska; Magdalena Gawlak; Jędrzej Warguła; Łukasz Kaczmarek (PLoS ONE, 2025)
In this study, we present descriptions of two new eutardigrade species and additionally a detailed description of new population of Mesobiotus cf. coronatus discovered in the Cotacachi-Cayapas National Park in Ecuador. The presented analysis is based on morphological and morphometric data using light and scanning electron microscopy; description of Macrobiotus sharopovi sp. nov. and the population of Mesobiotus cf. coronatus were also supported with genetic data (nuclear barcode sequences, i.e., 18S rRNA, 28S rRNA and ITS-2, and one mitochondrial COI sequence). Based on the egg morphology, Mac. sharopovi sp. nov. belongs to Mac. paulinae morpho-group and is most similar to Mac. papei, Mac. paulinae, Mac. polypiformis and Mac. shonaicus but differs from them mainly by some characters of eggs (number of egg processes on circumference, details of eggshell morphology and features of filaments and their number) and adults (size of cuticular pores). Based on such features as the presence of gibbosities and well visible dorsal sculpture, the second new species, i.e., Ramazzottius syraxi sp. nov. is the most similar to Ram. baumanni species complex, Ram. belubellus, Ram. saltensis and Ram. szeptycki but differs from them by gibbosities configuration and morphology of dorsal sculpture. Mesobiotus cf. coronatus, which belongs to Meb. harmsworthi morpho-group, is potentially a new species but due to unclear taxonomic position of nominal Meb. coronatus, a formal description of this taxon is not possible in the present study.